(untitled) (Stato, Chiese e pluralismo confessionale, 2023)
Constantine I The Great. The Emperor, the man, the leader ABSTRACT: History is not the teacher of life, but perhaps the reverse could be true if one looks at the emblematic events and proceedings of this interesting study conference, held at the University of Bari from 17 to 18 November 2022, in which the mysteries of the past are probed through the eyes of the present. The author reviews the salient features of the figure of Constantine I the Great as Emperor, Man and Commander to reach perplexing conclusions about his elevation to the honours of the Altars, especially in the Orthodox world. SOMMARIO: 1. Vita magistra historiae - 2. L’Imperatore - 3. L’uomo - 4. Il condottiero.